Addendum: Beyond the limits of 1D coherent synchrotron radiation (2018 New J. Phys.20 073035). (21st April 2021) - Brynes, A D; Smorenburg, P; Akkermans, I; Allaria, E; Badano, L; Brussaard, S; Danailov, M; Demidovich, A; De Ninno, G; Gauthier, D; Gaio, G; van der Geer, S B; et al.
Abstract: This paper is an addendum to reference  (Brynes et al 2018 New J. Phys. 20 073035), in which we studied the transverse emittance growth due to coherent synchrotron radiation (CSR) in the bunch compressor of a free-electron laser. Analytic results based on the theory of CSR were compared with results from experiment and simulation. Recent results have been published (Stupakov 2019 arXiv:1901.10745 ) which correct the theoretical emittance growth, predicting a smaller increase than that which was expected based on previous results. When comparing these new calculations with the emittance growth that was measured experimentally, and with 3D simulations, we find an improved agreement when the bunch compression approaches its maximum value.